2017
DOI: 10.1186/s12872-017-0605-3
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Adrenomedullin predicts 10-year all-cause mortality in community-dwelling patients: a prospective cohort study

Abstract: BackgroundSeveral studies found mid-regional pro-adrenomedullin (ProADM), the prohormone of the cardiovascular protein adrenomedullin, to be strongly associated with short-term mortality, mostly in the inpatient setting. We evaluated associations of ProADM levels with 10-year mortality in community-dwelling primary care patients with respiratory tract infections.MethodsThis is a post-hoc analysis using clinical and biomarker data of 134 primary care patients with respiratory tract infections. ProADM was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Our cohort of primary care patients, however, displayed little systemic inflammation and this may have deemed MR-proADM less clinically relevant. Studies on MR-proADM as a biomarker in respiratory tract infections in primary care are scarce [31]. Our findings of CRP and procalcitonin are in accordance with other studies [7, 32].…”
Section: Discussionsupporting
confidence: 92%
“…Our cohort of primary care patients, however, displayed little systemic inflammation and this may have deemed MR-proADM less clinically relevant. Studies on MR-proADM as a biomarker in respiratory tract infections in primary care are scarce [31]. Our findings of CRP and procalcitonin are in accordance with other studies [7, 32].…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were also reported by Klip et al[35] ADM was also found to be predictive of mortality in a cohort of community-dwelling patients. [36]…”
Section: Biomarkers For Prognosismentioning
confidence: 99%
“…Adrenomedullin (AMD) is a 52 amino acid peptide synthesized by a variety of tissues, including adrenal medulla, vascular endothelial cells, vascular smooth muscle cells and adipose tissue [ 1 3 ], and exhibits vasodilatative properties [ 4 ]. In addition to its hypotensive effects, biological actions of AMD include antioxidative and antiapoptotic but also metabolic effects, such as inhibition of insulin secretion in beta cells [ 4 ].…”
Section: Introductionmentioning
confidence: 99%